Hubungan Usia, Pendidikan, Pekerjaan Dan Perilaku Hidup Ekstrem Terhadap Dampak Kesehatan Masyarakat Di Desa Batu Bulan, Kecamatan Moyo Hulu, Kabupaten Sumbawa - Maitsa Fikri Nabila; Bagas Arya Nasution; Anisa Trihapsari; Febri Puji Lestari (Program Studi Teknik Sipil, Fakultas Teknik Universitas Teknologi Sumbawa, 2025)
This study aims to analyze the influence of age, education level, occupation, and extreme lifestyle on public health impacts in Batu Bulan Village, Moyo Hulu Subdistrict, Sumbawa Regency. Using a quantitative descriptive method with a cross-sectional approach, data were collected through direct interviews and observations, then analyzed using multiple regression via SPSS software. The t-test results showed that age, occupation, and extreme lifestyle significantly affected public health, while education level had no significant effect. The F-test indicated that the four variables collectively influenced public health. The most common illnesses experienced by the community were coughs and colds, with most respondents being smokers and working as farmers. These findings highlight the importance of social and behavioral-based interventions to improve community health.